COMPARISON AND ANALYSIS OF TWO METHODS OF AXIAL FATIGUE STRENGTH CALCULATION - ZHENG YuTian; LIU ShaoJun (Jixie qiangdu)
Comparative analysis of two methods of analysis shaft fatigue strength including Chinese Machine Design Handbook method and American National Standard namely AGMA（ American Gear Manufacturers Association） standard ANSIAGMA 6001-D97 method. This essayanalysisthesecalculation process about these two methods and set examples to find out there major difference and their adaption to different situations.